Effect of concurrent training on body composition and metabolic profile of obese people: A systematic review (Research, Society and Development, 2022)
The variously active lifestyle and therapeutic exercise interventions are considered the basis for the management of obesity. The objective of this work is to compare different methodological sequences of randomized clinical trials on endurance training (ET) and strength (TF), high-intensity interval training (HIIT) and concurrent training (CT) to improve body composition and induce physiological responses. The Web of Science, Pubmed, Science Direct databases were searched for studies that studied the effects of different sequences in concurrent training on body composition and physiological adaptations of a metabolic nature, using the combined descriptive arrangement elaborated for the search: (“Obesity People” OR “Sedentary”) AND “Body composition” AND “Concurrent training” (“Endurance” OR “Force” OR “Sliming”). The time range searched in the databases was 2017-2022. The quality of included studies was assessed using the Cochrane Handbook risk assessment tool. After a careful search, a total of 9 randomized and controlled studies were selected. The works consulted reported that there was no significant difference in body mass, lean body mass and percentage body mass index between the groups of elderly people; however, there was a significant difference in body fat percentage between the two obese and sedentary obese young adult groups of various age groups and sex. In this way, it is concluded that the CT is indicated and is another very advantageous strategy for interventions aimed at weight loss in obese young individuals.